(untitled) (Research, Society and Development, 2020)
The aim of the present study was to evaluate the leaching of different clomazone formulations as a function of straw density and different irrigation depths. The experiments were conducted in a completely randomized design, in a 2 x 6 factorial scheme, with four replications. Experiment I used two herbicides Gamit (1,260 g ha-1 of clomazone) and Gamit 360 CS (1,260 g ha-1 of microencapsulated clomazone), six straw densities (0, 5, 10, 15, 20, 25 t ha- 1). For experiment II, two Gamit herbicides (1,260 g ha-1 of clomazone) and Gamit 360 CS (1,260 g ha-1 of microencapsulated clomazone) were used, six irrigation depths (5, 10, 15, 20, 25 and 30 mm). Visual assessments of the percentage of intoxication were carried out at 7, 14, 21 and 28 days, the dry matter was determined at 28 days. The percentage of intoxication in soils contaminated with herbicide leachate at different straw densities (0 and 5 t ha-1) remained the same for clomazone herbicides in the conventional and microencapsulated formulation. However, when in microencapsulated formulation, a level of intoxication around 90% was observed, demonstrating the capacity it has to overcome the layer of straw. The increase in the water depth provided the greatest transposition of the herbicide by the physical barrier imposed by the straw, which reflected in the increase in the percentage of control. It was concluded that the leaching of clomazone when in microencapsulated formulation is greater than in conventional formulations, regardless of the physical barrier imposed by the straw and the applied water layer.